Pengukuran Kinerja Reksa Dana Syariah Campuran Dengan Metode Sharpe Ratio dan M2 Measure - Sonia, Lira; Purbayati, Radia; Mayasari, Ine; Djatnika, Djoni (Journal of Applied Islamic Economics and Finance, 2023)
This research was conducted to find out the performance of mixed-type sharia mutual funds in Indonesia during the 2017-2021 period. The performance measurement method uses the concept of calculating Risk Adjusted Return, which in this study specifically uses the Sharpe Ratio and M-Square Measure (M2) methods. The results of the calculation will be compared with market performance and analyzed. The results showed that in 2021 there were many mixed sharia mutual funds that outperformed the benchmark, namely 11 sharia mutual funds, while 2017 was the year that the least sharia mutual funds produced outperformed performance, namely there were only 2 sharia mutual funds. The following years produced a higher number than in 2017, such as in 2018 there were 7 sharia mutual funds with outperforming performance, also in 2019 there were 3 sharia mutual funds and finally in 2020 there were 5 sharia mutual funds whose performance outperformed the benchmark.